Phytochemical profiling and in vitro biological evaluation of white dragon fruit (Hylocereus undatus) peel fractions toward HeLa cell line - Krisridwany, Annisa; Sari, Sindi Novita; Winanta, Aji; Heresmita, Perdana Priya; Febriansah, Rifki (Jurnal Ilmiah Farmasi, 2026)
Background: Cancer is a complex disease characterized by dysregulated cell growth and the potential to invade surrounding tissues. Current therapeutic approaches continue to expand, including increasing interest in bioactive compounds derived from natural products. This study aims to evaluate the biological activity of ethanol, n-hexane, and ethyl acetate fractions of Hylocereus undatus (white dragon fruit) peel extract against the HeLa cervical cancer cell line.Method: The extraction process was performed using the maceration method, and phytochemical screening was conducted using stain reagents. The cytotoxicity test was carried out using the MTT assay with concentrations of 1000, 500, 250, 125, 62.5, and 31.25 µg/mL, while morphological changes were observed under an inverted microscope.Results: The phytochemical screening indicated that alkaloids, steroids, and triterpenoids were present in the n-hexane fraction; flavonoids and tannins in the ethanol fraction; and flavonoids, alkaloids, and tannins in the ethyl acetate fraction. The highest IC50 value (311.27 µg/mL) was observed on the n-hexane fraction compared to the other fractions. The HeLa cell line showed shrinkage after treatment with all fractions. Conclusion: Of the three tested fractions, cytotoxicity was observed solely in the n-hexane fraction, whereas the ethyl acetate and ethanol fractions remained inactive against HeLa cells.